The Influence of Business Strategy and Good Corporate Governance on Corporate Sustainability Performance: Coal Mining Listed on The Indonesia Stock Exchange - Robertus Maria Bambang Gunawan (Eduvest - Journal of Universal Studies, 2025)
The coal mining industry significantly contributes to Indonesia’s economic development, yet it continues to face complex challenges in achieving sustainability from environmental, social, and governance (ESG) perspectives. This research investigates the influence of business strategy and good corporate governance (GCG) on corporate sustainability performance (CSP) among coal mining companies listed on the Indonesia Stock Exchange (IDX). This study uses a quantitative research design to draw on secondary data from company annual reports, sustainability reports, and GCG disclosures published on the IDX official website. The analysis employs multiple linear regression to test the proposed hypotheses. The findings indicate that both business strategy and good corporate governance significantly positively affect the sustainability performance of the coal mining sector. These results suggest that aligning strategic business orientation with ESG principles and reinforcing governance structures are crucial for achieving sustainable performance. This study provides empirical evidence supporting the integration of sustainability practices within corporate strategy, and it emphasizes the importance of transparent governance in resource-intensive industries. The implications of this research are relevant for corporate leaders, policymakers, and sustainability advocates seeking to advance responsible business practices in the extractive industry.